Copycat Pi (Data Acquistion Tools) - Mohd. Nazri, Muhammad Ikhmal Hakim; Abdullah, Dalilah (Journal of Computing Technologies and Creative Content, 2019)
Copycat Pi is a modified raspberry pi that will be turn into a data acquisition tools. The function of the Copycat Pi is to copy all the data from source drive to the targeted drive. The method that will be involved when copying the data is logical acquisition method. For this project, the type of the file be copied is disk to disk. The copied also will be verified with md5 hashing to ensure the integrity of the disk. Evidence data from the crime scene is vulnerable to the modification or being delete if the forensic team did not act fast enough.